The Psychology of Faith in Mental Health - Mutiara Tanila (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
Faith and spirituality are increasingly recognized as crucial factors in supporting mental health. This study examines the role of faith in strengthening psychological resilience, regulating emotions, and providing social support, while also highlighting the ambivalent effects of religious struggles. A narrative review design is employed with a systematic search of PubMed, Scopus, and Google Scholar for articles published between 2019 and 2025. Fifteen peer-reviewed studies were analyzed qualitatively to identify thematic patterns. The findings reveal that faith provides meaning-making frameworks, enhances psychological flexibility, and fosters community support that reduces depression, anxiety, and stress. At the same time, religious struggles are associated with higher levels of distress, showing that faith has both protective and risk dimensions. The novelty of this work lies in synthesizing recent cross-cultural evidence, thereby expanding the psychology of religion beyond Western contexts. The conclusion emphasizes the importance of integrating culturally